RESPONSE OF TWO BREAD WHEAT VARIETIES YIELD TO MINERAL, BIO-AND ORGANIC FERTILIZERS - & Flayyah, Al-Hilfy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
To study the effect of mineral fertilizers (NPK), Organic and Bio-fertilizers on grain yield of bread wheat(Triticum aestivum L.). A field experiment was conducted during 2014-2015, 2015-2016 at the experimental farm of Field Crop Department, College of Agriculture, University of Baghdad ,Iraq. A split plot arrangement within RCBD, using four replications for two varieties at the main plots and 14 fertilizer treatments at the sub plots:T0 (control) ,T1 (mineral fertilizer as recommended), T2 (bio-fertilizer), T3 (organic fertilizer), T4 (bio+ organic fertilizers), T5(mineral fertilizer +bio- fertilizer), T6(50% mineral fertilizer + bio-fertilizer), T7 (25% mineral fertilizer+ bio-fertilizer), T8(mineral fertilizer+ organic fertilizer), T9(50% mineral fertilizer+ organic fertilizer), T10(25% mineral fertilizer+ organic fertilizer), T11 (mineral fertilizer+ organic fertilizer + bio-fertilizer), T12 (50% mineral fertilizer + organic fertilizer + bio-fertilizer), T13(25% mineral fertilizer + organic fertilizer + bio- fertilizer). The results showes the V. Buhooth 22 was superior in No. of spikes (436.2,474.9) spikem-2, No. of grains (65.73,70.96) grain spike-1, grain yield (5.52,5.79) ton h-1 and biological yield (14.90,15.51) ton h-1 for both seasons. The Integrated treatment T11 (mineral fertilizer + bio-fertilizer + organic fertilizer) was superior in grain yield (5.71,6.11) ton h-1,biological yield (15.35,15.92) ton h-1 for both seasons. It can be concluded a possibility to substitute a part of mineral fertilizers by bio+organic fertilizers.